(untitled) (De Legibus - Law Journal, 2025)
The ever-increasing proximity between the Criminal Justice administration system and media, in this post-modern “spectacle society” in which we live, may strike an almost osmosis, undermining the procedural preservation of fundamental safeguards, threatening vital State keystones, even the Rule of Law. Are we amid a populist rise, that will climax in the reductionist mediatization of Justice, converted in a superfluous ‘mis-en-scéne’? The Portuguese criminal Legislator succumbed to the populistic siren song, surrendering to ‘the People’, represented by the media and in their outcry for immediate and punitive Justice? This work aims to present some analytical outlines, to further and at length study, promoting the academic debate of these subjects.